Groundwater Quality in Nigerian Urban Areas: A Review (Global Journal of Science Frontier Research, 2014)
The status of the quality of groundwater in urban areas of Nigeria is reviewed in this paper. This is done against the backdrop of its current status, trend and identification of factors influencing the quality of urban groundwater and possible remedial measures in Nigeria. Studies have shown that Nigeria urban groundwater quality is influenced by the geology and geochemistry of the environment, rate of urbanization, industrialization, landfill/dumpsite leachates, heavy metals, bacteriological pollution, and effect of seasons. Remedial measures suggested include protection of water sources, proper handling of wastes and construction of sanitary landfills, control of all land use polluting activities, and treatment of water before is used for consumption. Continuous monitoring of groundwater quality is necessary to forestall any unpleasant consequences.
Keywords: groundwater; quality; pollution; concentrations; hand dug wells; boreholes